Manufacturing of Rotational Toroidal Shells in Coin Minting - Luís M. Alves; Paulo Alexandrino; Sónia Pereira (Eng, 2025)
A novel forming process was developed to create rotating elements in collector coins by shaping thin-walled tubes into toroidal shells in a single stage. This process introduces new aesthetic effects and functionalities to the coin market. By controlling the end-forming of a tube, a gap is created between the toroidal shell and the coin blank, allowing free rotation. The technique, a modification of conventional tube end inversion, results in distinct deformation mechanics. Through finite element modeling and experimentation, key process variables were identified, ensuring sound hollow toroidal shells with efficient rotation.